MANAJEMEN PENDIDIKAN KARAKTER DALAM METODE SENTRA - Hotimah, Husnul; Syafuri, Syafuri; Zohriah, Anis (LPPM Institut Pendidikan Nusantara Global, 2023)
The purpose of the research is to describe how the center method or Beyond Center and Circle Time Method is implemented in character educational management in Indria Islamic School Kindergarten Sepatan Timur Tangerang. This is qualitative research. It’s combined with management function which is we want to know about the preparation, the implementation, the evaluation and the supporting and the obstacle factors. The data collection technique used are observation, interviews and documentation. The data validity is used the source of triangulation, which means comparing and re-checking the degree of in the information obtained. The data analysis uses Miles and Huberman. The result of the study in Indria Islamic School Kindergarten Sepatan Timur Tangerang implements the center method in character educational management is effective and efficient. This is reflected for the plan preparation, implementation and the evaluation was very good. The supporting factors are the Al- Qur’an and Hadits as main guidelines of Islam. While inhibiting factor is the lack of literacy references and play creations.